2012
DOI: 10.12669/pjms.291.2688
|View full text |Cite
|
Sign up to set email alerts
|

Causes of short stature identified in children presenting at a tertiary care hospital in Multan Pakistan

Abstract: Objective: To determine the frequency of common causes of short stature in children presenting to the Children’s Hospital & the Institute of Child Health, Multan. Methodology: This cross sectional study was done in Pediatric Endocrinology department, the Children’s Hospital & the Institute of Child Health, Multan, from March to September, 2011. One hundred and sixty nine children with short stature presenting to the outpatient department meeting inclusion criteria were recruited after taking an informed consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 19 publications
7
37
1
Order By: Relevance
“…Primary hypothyroidism was seen in 9% (n=6) cases, while central hypothyroidism was present in only 1% in our study. Sultan et al in a Pakistani study reported hypothyroidism as a cause of short stature in 5.6% of their study population,14 while another local study by Rabbani et al reported it as 17% 15. Pan-hypopituitarism which is known to stunt growth was present in 6% of the patients, an Iranian study reported it as 3.5% 31.…”
Section: Discussionmentioning
confidence: 89%
“…Primary hypothyroidism was seen in 9% (n=6) cases, while central hypothyroidism was present in only 1% in our study. Sultan et al in a Pakistani study reported hypothyroidism as a cause of short stature in 5.6% of their study population,14 while another local study by Rabbani et al reported it as 17% 15. Pan-hypopituitarism which is known to stunt growth was present in 6% of the patients, an Iranian study reported it as 3.5% 31.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study 100 patients of short stature were enrolled, among them most common age group was 6-11 years, which is similar with other studies. 16,17 Present study had 47 males and 53 females. The male to female ratio was 0.92:1.…”
Section: Discussionmentioning
confidence: 98%
“…It is not similar with most of the studies done in different countries where males outnumbered the females. [17][18][19] Increased incidence of short stature in females in this study may be due to the fact that, there is increasing awareness among people about health seeking and most of the families have only 1-2 child. So, parents are giving similar emphasis on female and male child.…”
Section: Discussionmentioning
confidence: 99%
“…Turner syndrome which is present in one of 2000 female alive birth infants, accounts for one out of 60 cases of female short stature (4) . If a chronic disease in childhood is severe enough, they can lead to growth failure and short stature and they include; renal, and cardiac diseases, malignancy, cystic fibrosis and celiac disease (20). Celiac disease can result in short stature by causing malnourishment (4) especially in young children (21) .…”
Section: Figure1: Causes Of Short Staturementioning
confidence: 99%